Effect of Connection Losses on Fiber To The Building (FTTB) Network Activation - Nasrul, Nasrul; Maria, Popy; Zahra, Nurraudya Tuz; Gusmiati, Yosi (Brilliance: Research of Artificial Intelligence, 2024)
The Fiber To The Building (FTTB) technology uses fiber optic cables for high-speed data transmission in high-rise office buildings. However, connection loss in fiber optic cables, especially during network activation, can significantly affect the overall performance and reliability of the FTTB network. This study investigates the effects of connection loss on total attenuation in FTTB networks before and after activation, using Passive Optical Network (PON) technology. Simulations were performed on three subscriber scenarios with different treatments of drop core cables (no connection, one connection, two connections) and patch cord cables of different lengths (3m, 5m, 10m), each with additional variations in the number of connections. Attenuation measurements were taken before and after network activation, showing that increasing cable length and splices leads to higher attenuation and reduced network performance. For example, customer 1 with no connections had the lowest attenuation before activation of 19.68 dB and after activation of 19.57 dB with signal quality (ping ONU 11 ms, ping OLT 9 ms, and ping Google 31 ms) while customer 3 with the most connections had attenuation values before activation of 20.92 dB and after activation of 20.87 dB with signal quality (ping ONU 29 ms, ping OLT 28 ms, and ping Google 70 ms). This research emphasises the importance of link management and the length of cable used to minimize attenuation and ensure optimal network performance.